Aksesibilitas dan Literasi Digital Musisi Independen dalam Pemanfaatan Platform Believe Backstage - Rengga Ramayuda; Soni Reffali; Hinhin Agung Daryana (Grenek: Jurnal Seni Musik, 2025)
This study examines the experience of the band AidoAudio in utilizing the Believe Backstage platform for digital music distribution through a descriptive qualitative approach using a case study, involving semi-structured interviews and supporting documentation. Findings indicate that access to the platform is largely influenced by social networks and informal communication, while internal administrative measures, including establishing a label and managing legal documents, strengthen legitimacy and expand distribution opportunities. The band’s digital literacy is multilayered; technical-operational skills such as uploading releases are relatively well-mastered, but interpretative and strategic literacy, including the use of analytics and editorial pitching, remains limited. Administrative barriers and limitations in strategic literacy create a dual obstacle, meaning that available access is not always fully utilized. To address this, the band develops internal strategies including managing promotional materials, simple evaluations, and coordination with relevant parties to enhance distribution effectiveness. The study underscores that successful digital distribution for independent musicians requires the integration of administrative legitimacy, technical proficiency, and strategic literacy to fully and sustainably leverage the potential of the platform.